MEANING OF SOCIAL INTERACTION IN PANDEMIC FOR ELDERLY: A QUALITATIVE STUDY - maria theresia arie lilyana; Made Indra Ayu Astarini (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: The elderly belongs to the marginal cause not profitable and just be burden for productive age even though they still have an opportunity to growth as their old. Social interaction gave the meaning for elderly in their end of live. Limited social interaction, as a policy to decrease morbidity and mortality caused by Covid-19 interfered that activity for elderly. Objectives: The aim of the study was to description the elderly experience when limited social interaction become a policy during pandemic Covid-19. Methods: Research design used phenomenology to explore elderly’s experience when limited social interaction become a policy during the pandemic Covid-19. Data collected by interview until data saturated, 10 participants conducted in this research, data was analyse used thematic analysis by reading the transcript verbatim. Results: Limited social interaction for elderly in this study give the theme: the form of social interaction in the elderly, the feelings experienced by limiting social interaction and the benefits of social interaction for the elderly. Conclusion: Limited social interaction had an impact as feeling unhappy, boredom and sense of longing. Without the good intervention, it will interfere with the health and quality of life of the elderly